Membangun Struktur Khotbah yang Transformatif Menurut 2 Timotius 3:16-17 Bagi Generasi Muda Di Era 5.0 - Suwondo, Victorio Emmanuela Sammy; Baskoro, Paulus Kunto; Jani, Jani (Sekolah Tinggi Agama Kristen Diaspora, 2025)
Sermons are the primary means of conveying God's word in church life. However, sermons today often focus solely on theological information. Sermons should be transformative, bringing about real change in the mindset, attitudes, and behavior of listeners. This is so that today's younger generation can become doers of the Word, not just hearers. This study aims to examine how to build a transformative sermon structure based on the principle of 2 Timothy 3:16, which emphasizes four key functions of God’s Word: teaching, rebuking, correcting, and training in righteousness. Using a kualitatf deskritif method, this research highlights that transformative preaching is urgently needed by young people who live amidst digitalization, moral relativism, and identity crises. Preaching that is rooted in the Word of God, delivered in a communicative language, and contextualized to the digital life of the younger generation will serve as an effective means of shaping faith and Christlike character. This study is expected to contribute theoretically to the field of homiletics and practically to churches and preachers in designing sermons that are relevant, applicable, and transformative for the young generation in the Society 5.0 era.AbstrakKhotbah merupakan sarana utama penyampaian firman Tuhan dalam kehidupan gereja. Namun saat ini yang terjadi kotbah hanya berhenti dalam informasi teologis semata. Padahal kotbah harus bersifat transformatif, yaitu membawa perubahan nyata dalam pola pikir, sikap hati, dan perilaku pendengar. Supaya generasi muda sekarang dapat menjadi pelaku Firman dan bukan hanya pendengar Firman. Penelitian ini bertujuan untuk mengkaji bagaimana membangun struktur khotbah transformatif berdasarkan prinsip 2 Timotius 3:16, yang menekankan empat fungsi utama firman Allah: mengajar, menyatakan kesalahan, memperbaiki kelakuan, dan mendidik dalam kebenaran. Dengan metode kualitatif deskriptif, penelitian ini menegaskan bahwa khotbah transformatif sangat dibutuhkan generasi muda yang hidup di tengah arus digitalisasi, relativisme moral, dan krisis identitas. Khotbah yang berakar pada firman Allah, disampaikan dengan bahasa komunikatif, serta relevan dengan konteks kehidupan digital generasi muda, akan menjadi sarana efektif bagi pembentukan iman dan karakter Kristus. Penelitian ini diharapkan memberikan kontribusi teoritis dalam bidang homiletika serta manfaat praktis bagi gereja dan pengkhotbah untuk merancang khotbah yang relevan, aplikatif, dan transformatif bagi generasi muda di era 5.0.